2007
DOI: 10.1097/mph.0b013e31814d68c3
|View full text |Cite
|
Sign up to set email alerts
|

Does the Periodontal Health of Thalassemia Major Patients Have an Impact on the Blood Lipid Profiles?

Abstract: Cardiac symptoms and premature death from cardiac causes are still suggested to be a major problem in thalassemic patients. One of the main reasons for the cardiovascular events in thalassemia major (TM) patients has suggested having iron overload, in addition to other reasons such as hypoxia, abnormal lipoproteins levels, atherosclerotic conditions, etc. This study aims to investigate whether the periodontal health has an impact on the blood lipid levels. Twenty-four TM patients and sex-matched controls (C) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Conflicting results have been found regarding the association between thalassemia and periodontal disease. While no difference in plaque index, gingival index, or periodontal probing depth was found between thalassemia patients and healthy controls [30], other studies reported a worse periodontal condition in thalassemia [29,48,49]. These discrepant results might be explained by the age difference of the included participants between the studies.…”
Section: Anemia and Oral Healthmentioning
confidence: 81%
See 1 more Smart Citation
“…Conflicting results have been found regarding the association between thalassemia and periodontal disease. While no difference in plaque index, gingival index, or periodontal probing depth was found between thalassemia patients and healthy controls [30], other studies reported a worse periodontal condition in thalassemia [29,48,49]. These discrepant results might be explained by the age difference of the included participants between the studies.…”
Section: Anemia and Oral Healthmentioning
confidence: 81%
“…They showed that among SCD patients with a sickle cell crisis, having a dental infection was associated with a 72% increased likelihood of being admitted to a hospital. A preliminary report in thalassemia showed that triglycerides and cholesterol/high-density lipoprotein ratio correlated positively with the periodontal parameters, suggesting that periodontal health might affect the lipid profile of thalassemia patients [49].…”
Section: Anemia and Oral Healthmentioning
confidence: 97%
“…In 2007, Ay et al . (20), compared to the blood lipid levels and periodontal parameters (gingival index, plaque index, probing bleeding, probing depth) in 24 TM patients with 20 age-matched control patients, and found that all periodontal parameters were significantly higher in the TM patients. Siamopoulou-Mavridou et al .…”
Section: Discussionmentioning
confidence: 99%